High Remanent Magnetization Measured in Hydrothermally Altered Lavas. Issue 23 (6th December 2021) - Kanakiya, Shreya; Turner, Gillian M.; Rowe, Michael C.; Adam, Ludmila; Lindsay, Jan M.
Abstract: Magnetic surveys are used to identify and monitor hydrothermally altered regions on volcanoes. Commonly such magnetic data are interpreted on the premise that hydrothermal alteration consumes Fe‐Ti oxides in the host rocks, reducing their total magnetization. Here, we report a contrasting observation from Whakaari (White Island) volcano in New Zealand. We study the magnetic properties of 42 conduit‐filling and surficial lithologies that have undergone varying degrees of acid‐sulfate alteration. We find that while the induced magnetization of lavas decreases with hydrothermal alteration, some altered lavas have an order of magnitude higher remanent magnetization than fresh lavas. We discuss plausible mechanisms by which altered lavas can retain high remanent magnetization including the importance of magnetic mineralogy and grain size. Our results urge caution in correlating reduced magnetization with hydrothermally altered regions. Furthermore, they highlight the importance of measuring both the induced and remanent magnetization of samples used to interpret field‐scale data. Plain Language Summary: Magnetic surveys are used to find regions in volcanoes where hot fluids alter the rocks and weaken them, locate ore bodies, and for geothermal exploration. These regions are expected to show low total magnetization on the surveys because the alteration process could consume iron‐bearing magnetic minerals in these rocks. Here, we report a different observation from our laboratory experiments on rocks from Whakaari (White Island) volcano in New Zealand. The total magnetization of rocks is the sum of magnetization from (a) minerals that temporarily become magnetized when an external magnetic field is applied (induced magnetization) and (b) minerals that stay magnetized even without an external magnetic field (remanent magnetization). We find that sometimes altered rocks, despite low induced magnetization, can have higher remanent magnetization than fresh rocks. We discuss the potential causes for this. Given the importance of magnetic surveys in volcanic slope stability assessment and mineral and geothermal exploration, we suggest exercising caution in assuming that hydrothermally altered regions would necessarily be associated with low total magnetization. Key Points: Natural remanent magnetization dominates induced magnetization in volcanic rocks from Whakaari Hydrothermally altered lavas can carry higher remanent magnetization than fresh lavas Both induced and remanent magnetizations should be used to interpret field‐scale data